(untitled) (Research Nepal Journal of Development Studies, 2025)
When people get sick from environmental problems, they need money for treatment. This creates big challenges for families. This study examined how 9,600 people from across Nepal pay for health care when they have environmental health problems. The research used data from a national survey to analyze what families do when they need money for medical care. The study found that most families (85%) use their savings to pay for health care. Only 11% borrow money and 1% sell things they own. Surprisingly, poor families rely more on savings (86.6%) than rich families (82.9%). Rich families are more likely to borrow money because they have better access to loans. Environmental health problems make families use different ways to get money compared to other health issues. Chronic diseases require more complex ways of paying than simple illnesses. Families who own land are 50% more likely to borrow money rather than sell their land. These findings show that Nepal needs better health financing policies. Poor families need more help getting loans. The government should create special insurance for environmental health problems. Since environmental health issues will increase due to climate change, Nepal needs better systems to help families pay for treatment.